A Comparative Study on the Quality Characteristics of Traditional Masmin and Mechanical Kiln Prepared Masmin - S., David Kingston; C.B.T., Rajagopalasamy; G., Sugumar (Fishery Technology, 2025)
The quality characteristics of traditional masmin as well as masmin prepared in he mechanical kiln have been compared. The quality of the mechanical kiln prepared product is superior when compared to the traditional product.